1996
DOI: 10.1007/bf01438667
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-wave resonant-cavity measurements of the thermal diffusivity of air: A comparison between cavity-length and modulation-frequency scans

Abstract: The application of a thermal-wave resonant cavity to thermal-diffusivity measurements of gases has been investigated. The cavity was constructed using a thin aluminum foil wall as the intensity-modulated laser-beam oscillator source opposite a pyroelectric polyvilidene fluoride wall acting as a signal transducer. Theoretically, cavity-length and modulation-frequency scans both produce resonance-like extrema in lock-in in-phase and quadrature curves. These extrema can be used to measure the thermal diffusivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 17 publications
2
33
0
Order By: Relevance
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25] The thermal-wave resonant cavity (TWRC) has demonstrated to be a simple, reliable, and accurate technique to study the heat transport in a large variety of fluids. [12][13][14] This photothermal technique involves the use a lock-in amplifiers and filters that allow us measuring very low signals even in highly noisy environments. In its simplest configuration, the TWRC consists of three parallel layers: the first one is a thin film called heater, which is heated up with a laser beam of modulated intensity; while the second one is a fluid sample supporting the propagation of the temperature oscillations induces by the heater towards the pyroelectric detector (third layer) that records the amplitude and phase delay of the thermal-wave signal, in the form of a voltage.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25] The thermal-wave resonant cavity (TWRC) has demonstrated to be a simple, reliable, and accurate technique to study the heat transport in a large variety of fluids. [12][13][14] This photothermal technique involves the use a lock-in amplifiers and filters that allow us measuring very low signals even in highly noisy environments. In its simplest configuration, the TWRC consists of three parallel layers: the first one is a thin film called heater, which is heated up with a laser beam of modulated intensity; while the second one is a fluid sample supporting the propagation of the temperature oscillations induces by the heater towards the pyroelectric detector (third layer) that records the amplitude and phase delay of the thermal-wave signal, in the form of a voltage.…”
Section: Introductionmentioning
confidence: 99%
“…One of them is based upon the fact that the L dependence of Eq. ͑4͒ is such that their in-phase ͑IP͒ and quadrature ͑Q͒ signals exhibit maxima and minima such that their nth extrema are given by 3,4 L n…”
Section: Methodsmentioning
confidence: 99%
“…The main attractive aspect of this new photothermal technique, originally called thermalwave resonant cavity, and later, thermal wave interferometer ͑TWI͒ by some other authors, is that it is well suited for the investigation of the thermophysical properties of gases and liquids. This can be appreciated by the growing number of papers that have recently applied this new technique to the investigation of the thermal properties of gases [3][4][5][6] and liquids. 7 The reason the TWI technique is so attractive to the investigation of gases and liquids is evident from its operational principle, namely, the monitoring of the spatial dependence of intracavity thermal waves.…”
Section: Introductionmentioning
confidence: 99%
“…47,48 In the case of gases, most of the investigations have used photoacoustic detection, whereas most of the works with liquids so far have used photoacoustic detection and remote photothermal refractive index modulation techniques, such as the photothermal phase shift technique, thermal lens, and the photothermal optical beam deflection. An alternative photothermal technique for measuring the thermal properties of gases was first discussed by Bennet and Patty 49 and later explored by Shen and Mandelis, [50][51][52][53] who succeeded in demonstrating the feasibility of the pyroelectric detection of thermal wave propagating across an air gap between a pyroelectric sensor and another material acting as the source of thermal waves. These authors showed that the thermal diffusivity of air could be measured with very good accuracy using this configuration for detection of thermal waves.…”
Section: F Thermal Wave Interferometry "Twi…mentioning
confidence: 99%